STRUCTURAL DISCRIMINATION OF PURINES AND PYRIMIDINES BY PROTEINS THROUGH WATER-MEDIATED CONTACTS - S. USHA; KM. SARAVANAN (International Journal of Pharma and Bio Sciences, 2016)
Water molecules play an important role in the recognition and stabilization of protein-ligand interactions. The water molecules at binding sites bridge the protein and ligand and can make three or more hydrogen bonds when distance and bond angles are used as criteria to define hydrogen-bonding interactions. There exists a distinct structural similarity between purines and between pyrimidine moieties. In the present study, we have analyzed the contribution of the water-mediated hydrogen bonds in the structure wise discrimination of these nucleotide bases. Significant differences in the amino acid residue preferences and the ligand atom preferences were observed in the case of purine moieties, adenine and guanine. In pyrimidine nucleotides, the amino acid residue Serine was preferred in both cytosine and thymine contacts; Asparagine was preferred in both thymine and uracil; Aspartic acid was preferred in both uracil and cytosine water-mediated contacts. Cytosine O2 atom was highly preferred whereas the O4 atom was highly preferred in thymine and uracil interactions. Since, the water networks provide increased specificity and affinity, the ability to include water-binding sites into the interface between a drug and its target might prove useful in drug design strategies.